NURSES’ ACCEPTANCE AND USE OF ELECTRONIC MEDICAL RECORD (EMR) IN SELECTED PRIVATE HOSPITALS IN MALAYSIA: A CASE STUDY - Mohammad Nur Firdaus Bin Mohammad Zakaria; Nik Azliza bt Nik Ariffin (Journal of Islamic, Social, Economics and Development, 2022)
The amount of technology used in the healthcare industry is growing, changing quickly, and constantly. The advancement of technology was impacted, and medical professionals' equipment and instruments were altered in order to provide better patient care. Traditional paper-based records have been replaced by an Electronic Medical Records (EMR) system, which has replaced one of the technological equipment or instruments. However, hospital acceptance of EMRs has been fraught with difficulties, and it is a key factor in EMR failure. One such hurdle is the lack of user acceptance. Research reveals that nurses are the largest section of EMR hospital users. In the literature, however, the criteria that contribute to the use and acceptance of EMR in the user group are not sufficient. Consequently, a lack of understanding of elements that impact the acceptability of EMRs by nurses is a major concern raised in this study. This research is using a survey questionnaire as the research instrument. The objective of this research is to examine current practices of the electronic medical record (EMR) among nurses, to identify factors that influence the acceptance of electronic medical records (EMR) among nurses and to analyze challenges and barriers in electronic medical record (EMR) practices among nurses in the selected private hospitals. The contribution of this study is to enhance the experience and acceptability of the nurses as the key group using the EMR system in the healthcare provider.